Dennett family papers
Correspondence, receipts, notes, a certificate, and printed material of various members of the Dennett and Fenner families, though consisting chiefly of letters between Rev. Wilbur E. Dennett of Providence, R. I., and his second wife, Philena (Lena) Sweet (Fenner) Dennett, relating to personal and family affairs. Also includes several letters of Rev. Dennett's son, educator and historian, Tyler Dennett (1883-1949).
Collection material in English.
Keywords: Dennett, Wilbur Eugene -- Correspondence; Dennett, Philena Sweet -- Correspondence; Dennett, Tyler, -- 1883-1949 -- Correspondence; Dennett family; Fenner family; Providence (R.I.) -- Social life and customs; Rhode Island -- Social life and customs